Practicality and Validity of the Instructional Speaking Materials Developed Based on CLT - Sujariati Sujariati; Risman Wanci; Rampeng Rampeng (Yayasan Keluarga Guru Mandiri, 2024)
This study focuses on developing instructional speaking materials for the Non-English students department in the classroom setting. Besides, the objectives of this study were to develop a teaching model through CLT-Based and develop the existing speaking materials into a new design course book or module of instructional speaking materials while finding out how the practicality and validity of the new teaching module or a new course book of instructional speaking materials based on CCLT-Based. This study was conducted at Universitas Muhammadiyah Makassar. The research methodology is research design and development (RD). The data collection is conducted with questionnaires and interviews. The collected and gathered data are analyzed through quantitative and qualitative methods. The quantitative data are gained from distributing questionnaires to students and lecturers to understand the new teaching model and the new course book content. The results of the questionnaire and interview show the qualitative aspect. The experts’ judgments, comments, and opinions poured on practical and valid data by two experts related to their assessments of the materials using the Likert scale. The result findings of this study presented a new teaching model of CCLT to help another lecturer in teaching speaking English in the context of Non-English education, presented instructional speaking materials of CCLT that have been developed through CLT-Based instruction to help students to help students in improving their daily speaking around the activities in campus.